Analysis of Policy and Business Competition As An Industrial Development Strategy in Indonesia: A Bibliometric Study Using Vosviewer - Muh Rizal S; Zulfikar Zulfikar; Fakhrian Arsyam Gultom (Pinisi Business Administration Review, 2026)
Using bibliometric methods, this study aims to evaluate the role of competition policy as a strategic tool in the development of the industry in Indonesia. This study maps 50 scientific articles from the Scopus and Google Scholar databases (period 2015–2025) based on three modes of analysis: network visualization, visualization density, and visualization overlay. The network visualization results show that four main interconnected clusters have formed, with the financial cluster (loans, banks, and credit) as the strongest network center. The density map shows a significant lack of research on effectiveness, renewable energy, and governance. The visualization overlay shows a shift in trends from conventional market structure issues to policy implementation, policy interaction, and the role of policymakers. This study found that industrial development strategies in Indonesia require synergy between competition policy and industrial policy. This is known as the competition-industry policy relationship. One of the main recommendations is the importance of creating a formal coordination mechanism between the KPPU and the technical departments, as well as prioritizing the quantitative measurement of government impact in important sectors such as renewable energy.